2016
DOI: 10.1007/s11904-016-0332-x
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the Liver: What This Means for Patients with HIV

Abstract: As the HIV population continues to live longer as a result of antiretroviral therapy, liver-related mortality has become one of the leading causes of non-AIDS related death in this patient population. The liver possesses a remarkable regenerative capacity but undergoes complex biological changes in response to aging and inflammation that result in decreased cellular regeneration and a tipping of the scales towards fibrogenesis. Patients with HIV infection have serological evidence of ongoing inflammation, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 108 publications
1
15
0
Order By: Relevance
“…Age is a well-known risk factor for LF in non-alcoholic fatty liver disease (NAFLD) and HCV-infected patients (Chan, Patel & Choi, 2016). However, data about age-related fibrosis in the HIV mono-infected population are scarce (Rockstroh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age is a well-known risk factor for LF in non-alcoholic fatty liver disease (NAFLD) and HCV-infected patients (Chan, Patel & Choi, 2016). However, data about age-related fibrosis in the HIV mono-infected population are scarce (Rockstroh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism, however, remains unknown. The decreased regenerative capacity, microbial translocation and HIV-induced immunologic dysfunction as well as chronic inflammation may play non-mutually exclusive roles (Chan, Patel & Choi, 2016). This result was also in line with our other finding, the identified remarkable negative association between LS and CD4/8 ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manuscript to be reviewed BMA revealed age as the most important predictor of LS. Age is a well-known risk factor for LF in non-alcoholic fatty liver disease (NAFLD) and HCV-infected patients (Chan et al 2016). However, data about age-related fibrosis in the HIV mono-infected population are scarce (Rockstroh et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, HIV and HCV coinfection leads to faster progression to fibrosis and cirrhosis in addition to an increased risk of hepatocellular carcinoma compared with HCV monoinfection. 32 However, a recent meta-analysis concluded that effective antiretroviral therapy may reduce liverrelated mortality among patients with dual infection. 33 Most cases of HIV-HCV coinfection occur in patients who use illicit intravenous drugs.…”
Section: Liver Diseasementioning
confidence: 99%